Long-term systemic angiotensin II type 1 receptor blockade regulates mRNA expression of dorsomedial medulla renin-angiotensin system components - Gilliam-Davis, Shea (American Physiological Society, 2011)
In Fischer 344 (F344) rats, renin-angiotensin system (RAS) blockade for 1 yr with the angiotensin II type 1 (AT(1)) receptor blocker L-158,809 prevents age-related impairments in metabolic function, similar to transgenic rats with low glial angiotensinogen (Aogen). Brain RAS regulation may contribute to the benefits of long-term systemic AT(1) antagonism. We assessed the mRNA of RAS components in the dorsomedial medulla of F344 rats at 3 (young; n = 8) or 15 mo of age (old; n = 7) and in rats treated from 3 to 15 mo of age with 20 mg/l of the AT(1) receptor antagonist L-158,809 (Old+L; n = 6). Aogen and renin mRNA were lower in the young compared with old group. Angiotensin-converting enzyme (ACE) mRNA was lower in the old and Old+L compared with the young group. ACE2 and neprilysin expression were significantly higher in Old+L compared with young or old rats. AT(1b), AT(2), and Mas receptor mRNA were higher with treatment. Leptin receptor mRNA was lower in the old rats and this was prevented by L-158,809 treatment. Dual-specificity phosphatase 1 (DUSP1) mRNA was highest in the Old+L group. Aggregate correlate summation revealed a positive relationship for Mas receptor mRNA with food intake. The findings provide evidence for regulation of dorsomedial medullary renin and Aogen mRNA during aging. Long-term AT(1) receptor blockade increases the mRNA of the enzymes ACE2 and neprilysin and the MAS receptor, which could potentially shift the balance from ANG II to ANG-(1–7) and prevent age-related declines in the leptin receptor and its signaling pathway.